A drug–drug conditioning paradigm reveals multiple antipsychotic–nicotine interactions. (April 2017) - Feng, Min; Sparkman, Nathan L; Sui, Nan; Li, Ming
Clinical studies indicate a reciprocal impact between nicotine use and antipsychotic medications in patients with schizophrenia. The present study used a conditioned avoidance response (CAR) test (a behavioral test of antipsychotic effect) and examined the specific drug–drug interactions between nicotine and haloperidol or clozapine. Following acquisition of the avoidance response, rats were first tested under either vehicle, nicotine (0.2, 0.4 mg/kg, sc), haloperidol (0.025, 0.05 mg/kg, sc), clozapine (5.0, 10.0 mg/kg, sc), or a combination of nicotine and haloperidol or nicotine and clozapine for seven consecutive days. Afterward, they were challenged with nicotine (0.2 mg/kg), haloperidol (0.025 mg/kg), or clozapine (5.0 mg/kg) in the CAR to assess if haloperidol or clozapine affected the behavioral effect of nicotine on avoidance response and if nicotine altered the avoidance suppressive effect of haloperidol and clozapine. During the seven avoidance drug test days, nicotine did not alter the avoidance suppressive effect of haloperidol or clozapine. However, in the challenge test, prior nicotine treatment (0.2 mg/kg) attenuated haloperidol's (0.05 mg/kg) sensitized effect on avoidance response. On the other hand, prior haloperidol treatment increased nicotine's (0.2 mg/kg) avoidance disruptive effect, and even engendered nicotine 0.4 mg/kg to exhibit an "acquired" avoidance suppressive effect. The combined nicotine and clozapine treatment did not produce any detectable interactive effects on avoidance response and motor activity. These findings suggest that nicotine is capable of altering the long-term antipsychotic efficacy of haloperidol, while haloperidol can alter the behavioral effects of nicotine. Clozapine and nicotine are less likely to influence each other.